Assessed occupational exposure to chlorinated, aromatic and Stoddard solvents during pregnancy and risk of fetal growth restriction. Issue 8 (15th June 2015) - Desrosiers, Tania A; Lawson, Christina C; Meyer, Robert E; Stewart, Patricia A; Waters, Martha A; Correa, Adolfo; Olshan, Andrew F
Abstract : Objectives: Previous experimental and epidemiological research suggests that maternal exposure to some organic solvents during pregnancy may increase the risk of fetal growth restriction (FGR). We evaluated the association between expert-assessed occupational solvent exposure and risk of small for gestational age (SGA) infants in a population-based sample of women in the National Birth Defects Prevention Study. Methods: We analysed data from 2886 mothers and their infants born between 1997 and 2002. Job histories were self-reported. Probability of exposure to six chlorinated, three aromatic and one petroleum solvent was assessed by industrial hygienists. SGA was defined as birthweight<10th centile of birthweight-by-gestational age in a national reference. Logistic regression was used to estimate ORs and 95% CIs to assess the association between SGA and exposure to any solvent(s) or specific solvent classes, adjusting for maternal age and education. Results: Approximately 8% of infants were SGA. Exposure prevalence to any solvent was 10% and 8% among mothers of SGA and non-SGA infants, respectively. Among women with ≥50% probability of exposure, we observed elevated but imprecise associations between SGA and exposure to any solvent(s) (1.71; 0.86 to 3.40), chlorinated solvents (1.70; 0.69 to 4.01) and aromatic solvents (1.87; 0.78 to 4.50). Conclusions: This is the first population-based study in the USA to investigate the potential association between FGR and assessed maternal occupational exposure to distinct classes of organic solvents during pregnancy. The potential associations observed between SGA and exposure to chlorinated and aromatic solvents are based on small numbers and merit further investigation.